Role of miR-144-5p in modulating lipid metabolism and potentially alleviating obesity via the PGC-1α/AMPK pathway - Yu, Siriguleng; Liu, Chaoqun; Lv, Hong; Guo, Zhijun; Yao, Hongqiang; Wen, Xin; Xiu, Ying; Gao, Wa; Li, Ziyi; Yu, Wen; Niu, Yaru; Jin, Junjian (Frontiers in Veterinary Science, 2025)
IntroductionMiR-144-5p is differentially expressed in plasma exosomes from Bactrian camels of varying body sizes, with GO and KEGG analyses indicating that its target genes play crucial roles in lipid metabolism. PGC-1α, confirmed as a key target through RNA pull-down and dual-luciferase reporter assays, is a significant regulator of this process. This study aims to investigate the impact of miR-144-5p on lipid metabolism in a mouse model of high-fat diet (HFD)-induced obesity to elucidate the mechanistic pathways involved.MethodsMale C57BL/6 mice were assigned to groups and fed either a control diet or an HFD for 12 weeks, which was followed by a 3-week intervention with miR-144-5p. Various metabolic parameters and gene expressions were evaluated to determine the effects of this treatment.ResultsThe treatment significantly reduced diet-induced adiposity and decreased inflammatory responses. Additionally, it inhibited PGC-1α expression in the liver tissue of HFD-fed mice. There was an increase in CPT1 activity and fatty acid β-oxidation rate, along with the downregulation of FASN mRNA expression and the upregulation of CPT1 and ACOX1 expression, promoting fatty acid oxidation.DiscussionThese findings suggest that miR-144-5p exerts anti-obesity effects by enhancing fatty acid oxidation, likely through modulation of the PGC-1α/AMPK signaling pathway. This study provides new insights into potential miRNA-based therapeutic strategies for obesity and related metabolic disorders.